Controllable in-situ preparation of high-coverage horizontal TiO2 nanosheet array - Wang, Junqi; Zou, Xiaoping; Zhu, Jialin; Cheng, Jin; Bai, Xiao; Yao, Yujun; Chang, Chuangchuang; Yu, Xing; Liu, Baoyu; Zhou, Zixiao; Li, Guangdong; Chen, Dan (Chemical physics letters, 2021)
[Display omitted] •In-situ controllable preparation of horizontal TiO2 nanosheet array is realized.•The formation of horizontal TiO2 nanosheet array is interpreted.•High-coverage TiO2 nanosheet array is used as an ETL to prepare PSCs. TiO2 is an important electron transport material in perovskite solar cells (PSCs). Some researchers have prepared dense TiO2 particles and mesoporous TiO2, but there are few reports on preparation of TiO2 nanosheets for solar cells. We have prepared in-situ controllable TiO2 nanosheet array on the fluorine-doped tin oxide (FTO) substrate with multiple spin-coating method, and the nanosheets were horizontally arranged in order with good shape consistency. Our research provides references for the preparation of solar cells with TiO2 nanosheets as electron transport layer (ETL).